Nation building in post-conflict settings: Evidence from South Africa - Thomas Gautier; Daniela Horta-Saenz; Gianluca Russo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
How do states rebuild nations after a major conflict? Truth and Reconciliation Commissions (TRCs) have emerged as one of the most common interventions to achieve this objective. Despite their popularity, little is known about their efficacy to foster reconciliation and nation building. We fill this gap by studying the seminal TRC established in South Africa after the end of the Apartheid. To measure exposure to TRC across South African municipalities, we leverage quasi-random variation in media coverage of the TRC message. South African municipalities with higher historical exposure to TRC on media have lower levels of violence today. This effect is driven by improved nation building and higher trust towards post-Apartheid institutions. Exploiting daily variation in TRC hearings and mediatic exposure in the short run, we bolster our interpretation that our long-run results are forged in the years of TRC activity. The same evidence suggests that our results are driven by the coverage of TRC on media as opposed to generic media exposure.
Keywords: D74; F63; O55; 330; nation building; post-conflict reconciliation; trust; South Africa; Truth and Reconciliation Commission